2013
DOI: 10.1126/science.1238017
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Grain Growth Induced by Cyclic Heat Treatment

Abstract: In polycrystalline materials, grain growth occurs at elevated temperatures to reduce the total area of grain boundaries with high energy. The grain growth rate usually slows down with annealing time, making it hard to obtain grains larger than a millimeter in size. We report a crystal growth method that employs only a cyclic heat treatment to obtain a single crystal of more than several centimeters in a copper-based shape-memory alloy. This abnormal grain growth phenomenon results from the formation of a subgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
111
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 250 publications
(114 citation statements)
references
References 27 publications
2
111
1
Order By: Relevance
“…[16][17][18][19][20] Omori and coworkers proposed a cyclic heat treatment, leading to abnormal grain growth (AGG) in Cu-Al-Mn and Fe-Mn-Al-Ni SMAs, resulting in a so-called bamboo-like microstructure, which is characterized by grain boundaries having a predominant alignment perpendicular to the loading direction. 4,20,21 These bamboo-like microstructures exhibit distinctly improved functional properties. 15,17 Concerning an intended industrial application of Fe-MnAl-Ni SMAs as damping devices embedded in conventional constructions designed from structural materials, in-depth knowledge of the weldability of these alloys is important to effectively implement welding and post-welding treatments, i.e.…”
mentioning
confidence: 99%
“…[16][17][18][19][20] Omori and coworkers proposed a cyclic heat treatment, leading to abnormal grain growth (AGG) in Cu-Al-Mn and Fe-Mn-Al-Ni SMAs, resulting in a so-called bamboo-like microstructure, which is characterized by grain boundaries having a predominant alignment perpendicular to the loading direction. 4,20,21 These bamboo-like microstructures exhibit distinctly improved functional properties. 15,17 Concerning an intended industrial application of Fe-MnAl-Ni SMAs as damping devices embedded in conventional constructions designed from structural materials, in-depth knowledge of the weldability of these alloys is important to effectively implement welding and post-welding treatments, i.e.…”
mentioning
confidence: 99%
“…Fortunately, the reversible transformation strain can be significantly improved by microstructure tailoring in Cu-Al-Mn SMA with high cold-workability and machinability. Cu-Al-Mn-based SMAs with bamboo-like grains [13][14][15] or columnar grains 16,17 have shown enhanced pseudoelasticity and fatigue resistance. For a columnargrained Cu-Al-Mn alloy, it shows a pseudoelasticity of more than 10%, which is comparable with that of single-crystalline one.…”
mentioning
confidence: 99%
“…The present Cu-Al-Mn is composed of inexpensive raw materials and, more importantly, has many unique advantages, including high ductility, 27 high machinability, 27 improved fatigue life, 16 grain size tunability, 26 and transformation temperature tunability. 28 It has been reported that the near o1004-oriented single crystal exhibits very large ε SE approaching 10%.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained plates were subjected to cyclic heat treatment (see Supplementary Figure S1a) to obtain single crystals by inducing abnormal grain growth. 26 The plates (shown in Supplementary Figure S1b) were subsequently annealed at 473 K for 15 min to stabilize the MT behavior between the cubic (L2 1 ) parent and monoclinic (18R, now often termed 6M) martensite phases. 27,28 As shown in Supplementary Figure S2, it was confirmed that the obtained Cu-17Al-15Mn does not undergo the thermally induced MTs in the temperature range 4-300 K.…”
Section: Methodsmentioning
confidence: 99%